G-jitter induc ed free convection over a vertical flat plate - Nawaf H. Saeid (Universitas Gadjah Mada, 2006)
The effect of the periodic oscillation of the gravitational field, known as g-jitter, on the free convection from a vertical plate is investigated in the present paper. The problem has been simplified by the laminar boundary layer and Boussinesq approximations. The fully implicit finite-difference scheme is used to solve the dimensionless system of the governing equations.The results for laminar flow of air (Pr = 0.72) and water (Pr = 7.00) are presented for different values of the amplitudes and frequencies of the g-jitter. The results presented show the steady periodic variation of Nusselt number and the friction coefficient with the amplitude and frequency of the gravitational acceleration oscillation. It is found that the Prandtl number as well as the amplitude and the frequency of the oscillating gravitational acceleration affect considerably the periodic oscillation of the Nusselt number and the skin friction on the vertical plate.